Eksplorasi Bakteri Penghasil Enzim Protease pada Air Rawa Tanjung Senai Indralaya Sumatera Selatan - Ace Baehaki; Rodiana Nopianti; Erwin Saputra; Nuni Gofar (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Baehaki A, Nopianti R, Saputra E, Gofar N. 2019. Exploration of protease enzyme producing bacteria from water in tanjung senai swamp Indralaya South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 121-131. Palembang: Unsri Press. Protease is a complex enzyme that plays a role in its application in the physiological field and commercial products. The aims of this research were to protease enzyme producing bacteria, to know the protease enzyme activity of bacteria isolate from water swamp and identify protease enzyme producing bacteria. This research was conducted by using laboratory experimental method and the data was analyzed descriptevely. The result of this research indicates that the Tanjung Senai AR1TS1 show the activity of protease enzyme and produce the highest proteolitic index among the other samples. Basedon Gram staining test, morphology of bacterial cell, motility test, catalase test, suger fermentation tes and H2S, oxigen needed test that kind of bacteria for AR1TS1 isolate was Liseria.Keywords: bacteria, protelitic, swamp, water